Answer:
12
7
2
- 3
- 8
Step-by-step explanation:
f ( - 2 )
= 2 - 5 ( - 2 )
= 2 - ( - 10 )
= 2 + 10
= 12
f ( - 1 )
= 2 - 5 ( - 1 )
= 2 - ( - 5 )
= 2 + 5
= 7
f ( 0 )
= 2 - 5 ( 0 )
= 2
f ( 1 )
= 2 - 5 ( 1 )
= 2 - 5
= - 5 + 2
= - 3
f ( 2 )
= 2 - 5 ( 2 )
= 2 - 10
= - 10 + 2
= - 8
Answer:
yes it is
Step-by-step explanation:
anything took to zerk is zero, 1 is higher thsn zero
Answer:
Step-by-step explanation:
g(2) = g(–2) = g(5) is never true for the step function. One " = " symbol per pair of g values, please.
The step function, which you're calling "g(x)," is 0 from -infinity up to but not including 0. It's 1 from x just greater than 0 through infinity.
Thus:
g(2) = 1 because x is greater than 0.
g(-2) = 0 because x is less than 0.
g(5) = 1 because x is greater than 0.
Answer:
k < 3/7
Step-by-step explanation:
Step 1:Sinplify both sides of the inequality
10k <-4k+6
Step 2: Add 4k to both sides
10k + 4k < -4k + 6 + 4k
14k < 6
Step 3:Divide both sides by 14
14k/14 < 6/14
k <3/7
Note:Provided by Mathpapa an Algebra caculator